Las cinco vías y la “verdad fundamental” de la Metafísica tomista (2022)
Metaphysics is the science that studies the being qua being; all reality, under its prism, is contemplated according to its relation to the act of esse. The notion of being is, in turn, the fulcrum that allows Metaphysics to ascend to God (Being by essence) and, from Him, to descend to creatures (beings by participation). In the present study we ask ourselves about the starting point of Metaphysics understood as Ontology: where does the metaphysical notion of being come from? What is its link with the experience of ordinary man? The knowledge of the being and, therefore, of its formal constitutive, which is the esse, is already presupposed, although in a confused, implicit way, in the everyday experience of man; the metaphysical notion of being is the explanation of a knowledge in which man is already connaturally installed. The thesis that we defend here, following Friar Norberto del Prado, O. P., is that the transition from this latent knowledge of the being as primum cognitum to its scientific explanation in the notion of being as terminus metaphysicalis takes place through the five ways of Thomas Aquinas (Summa Theologiae, I, q.2, a.3). In each of the ways, from its very starting point, the thesis of the act-potential composition of created beings between essentia and esse is already present — albeit in a concealing way — and, consequently, a certain knowledge of the being and of the mystery of esse. In our study, we will show how this thesis — which, together with the identity between essentia and esse in the First Cause, constitutes what Norberto del Prado calls the “fundamental truth of Christian philosophy” — is already exerting its influence on the five ways. Finally, by way of conclusion, we will show how the five ways are condensed in the fourth way, and how through it — which is already presupposed in the starting point of all the others — the transition from the ordinary knowledge of man to the scientific notion of entity takes place.